Unveiling the Shortcomings of Social Forestry Programs in Indonesia: A Critical Analysis of Farmer Empowerment Initiatives - Lawasi, Moh Andika (Department of Forestry, Faculty of Agriculture, University of Lampung, 2024)
Since being designated a national strategic program under President Joko Widodo’s administration, social forestry has yet to significantly alleviate poverty or improve the welfare of communities around forests. Despite the ambitious goal of allocating 12.7 million ha through various schemes such as community forests, village forests, customary forests, community plantation forests, and forestry partnerships, the welfare indicators for forest farmers remain largely unchanged. An in-depth investigation into the shortcomings associated with this program is necessary to uncover why it has yet to achieve its fundamental objectives. A comprehensive literature review involving critical analysis of various sources-including Google Scholar, Scopus, government websites, books, and other materials totaling 95 references, was conducted to examine the various dimensions influencing this program. The results reveal several impediments, including inadequate financial support and fragmented stakeholder collaboration, insufficient operational supervision in program implementation, weak motivation and capacity in institutional management, access inequality, conflict management, and underdeveloped post-harvest processing and networking capacities. Knowledge, technology, technical management, and policy information inputs are also insufficient. Addressing these issues requires a holistic approach, beginning with enhanced technical assistance, stronger program oversight, better institutional management, and improved capacities for market-oriented management of social forestry products and services. Keywords: critical analysis, farmer empowerment, forest management, marginalized groups, social forestry